Pengaruh Media Sosial Terhadap Citra Merek Dan Niat Beli - Natalia Suwarsih; Theresia Gunawan; Istiharini Istiharini (COSTING : Journal of Economic, Business and Accounting, 2021)
Currently half of the world's population uses various social media platforms, so social media is a source of commercial activity. This study aims to determine the effect of social media marketing on brand image on purchase intention of generation Z at a university with brand image as a mediation variable. The method used in this research is to use descriptive quantitative analysis, descriptive that is to explain, analyze and find out the value of a variable against other variables. While the quantitative research method is to examine the population or sample where the sample is taken randomly to collect data with research instruments to test a hypothesis. The results of this study are that there is a positive effect of social media marketing on brand image, there is a positive effect of brand image on purchase intention of generation Z, there is a positive effect of social media marketing on purchase intention of Generation Z, and there is also a positive influence of social media on generation Z purchase intentions by mediating brand image Keywords: Social Media Marketing, Brand Image, Purchase Intention, Generation Z